2019
DOI: 10.1016/j.compositesb.2019.106992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of YIG nanoparticle size and clustering in proximity-induced magnetism in graphene/YIG composite probed with magnetoimpedance sensors: Towards improved functionality, sensitivity and proximity detection

Abstract: Proximity-induced magnetism (PIM) in graphene (Gr) adjacent to magnetic specimen has raised great fundamental interests. The subject is under debate and yet no application is proposed and granted. In this paper, toward accomplishment of fundamental facts, we first explore the effect of particle size and clustering in the PIM in Gr nanoplates (GNPs)/yttrium iron garnet (YIG) magnetic nanoparticle (MNP) composite. Microscopic analyzes suggest that fine MNPs distributed uniformly on the GNPs have higher saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In this context, there are many reports on the surface modification of MI sensors by coating layers with different magnetization and conductivities. , All articles have reported the increase in the MI ratio, and the physical origins are well-discussed through the decrease of surface roughness and the closed magnetic flux path and magnetic exchange interactions between sensors and coated magnetic layers. , Also, some reports have used Gr-based materials and reported the better performances of their sensor device. ,, For example, the vertical Gr sheets may redistribute the surface magnetic field, which is good for improving the transverse permeability, or the MnFe 2 O 4 –Gr oxide nanocomposite increased the MI ratio due to the suppressed physical motion of the MnFe 2 O 4 NPs on the Gr sheet, as well as the enhanced effective anisotropy of the sample . Very recently, we coated the (Gr nanoplates)/(yttrium iron garnet) (GNPs/YIG) composite on a magnetic ribbon and showed that the proximity-induced magnetism (PIM) in Gr adjacent to magnetic YIG influences the magnetization of the GNPs to make them a wholly magnetized plane . Such a magnetized plane can be mounted on the surface of ribbon MI sensors, and thereby the MI response is enhanced against the external applied magnetic field significantly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, there are many reports on the surface modification of MI sensors by coating layers with different magnetization and conductivities. , All articles have reported the increase in the MI ratio, and the physical origins are well-discussed through the decrease of surface roughness and the closed magnetic flux path and magnetic exchange interactions between sensors and coated magnetic layers. , Also, some reports have used Gr-based materials and reported the better performances of their sensor device. ,, For example, the vertical Gr sheets may redistribute the surface magnetic field, which is good for improving the transverse permeability, or the MnFe 2 O 4 –Gr oxide nanocomposite increased the MI ratio due to the suppressed physical motion of the MnFe 2 O 4 NPs on the Gr sheet, as well as the enhanced effective anisotropy of the sample . Very recently, we coated the (Gr nanoplates)/(yttrium iron garnet) (GNPs/YIG) composite on a magnetic ribbon and showed that the proximity-induced magnetism (PIM) in Gr adjacent to magnetic YIG influences the magnetization of the GNPs to make them a wholly magnetized plane . Such a magnetized plane can be mounted on the surface of ribbon MI sensors, and thereby the MI response is enhanced against the external applied magnetic field significantly.…”
Section: Resultsmentioning
confidence: 99%
“…56 Very recently, we coated the (Gr nanoplates)/(yttrium iron garnet) (GNPs/YIG) composite on a magnetic ribbon and showed that the proximity-induced magnetism (PIM) in Gr adjacent to magnetic YIG influences the magnetization of the GNPs to make them a wholly magnetized plane. 8 Such a magnetized plane can be mounted on the surface of ribbon MI sensors, and thereby the MI response is enhanced against the external applied magnetic field significantly. However, in the case of Gr/Ni composite, the difference in the magnetization of composites is related to the difference in the amount of magnetic particles in the composite and not only PIM.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface quality is a decisive factor in determining the GMI property. Based on these facts, plenty of works based on surface treatment have been done to further improve the GMI characteristics of amorphous materials, such as: surface treatment by using yttrium iron garnet magnetic nanoparticles [33], surface coating [30,34], surface ultrasound treatment [35], ion or ray irradiation [36,37], roughness modification [29], stress annealing [9,10], current annealing [8,11]. Besides, by immersing Fe and FeNi thin films into aromatic solvents, a prominent magnetic anisotropy variation has been observed [38].…”
Section: Introductionmentioning
confidence: 99%